Exploring the factors at play to make wastewater biorefineries a reality - Verster, Bernelle (Centre for Bioprocess Engineering Research, 2019)
This thesis concerns the topic of wastewater biorefineries (WWBR), in which wastewater is not seen simply as a waste stream to be cleaned but as a valuable material flow to be converted into bioproducts, while still meeting discharge limits at the end. To set the scene, similar developing approaches to valorise wastewaters globally are reviewed. Wastewaters in South Africa are reviewed and categorised with regards to their potential to serve as raw material, in terms of their volume, concentration and complexity. Bioproducts possible from wastewater is reviewed and evaluated. The wastewater biorefinery is conceptualised in the context of current wastewater treatment technologies and a set of evaluation criteria is developed. A multi-reactor setup is suggested in which wastewater is used, in series, as substrate by heterotrophic microbes like bacteria, photo-mixotrophic organisms like algae, macrophytes and fungi. Each reactor group is considered in detail and evaluated with regards to its suitability to the wastewater biorefinery, leading to selection of appropriate reactor designs. Stoichiometric mass balances of all unit operations are established, showing the material value flows, and combined to model this multi-bioreactor approach. Subsequently the model is tested against literature data. Finally, the applicability of the wastewater biorefinery concept for certain waste streams is assessed. The thesis contributes to the current body of knowledge in the following ways: 1. Introduction of the concept of the wastewater biorefinery (WWBR) 2. Provision of a potential preliminary guide for classification of wastewaters for use in the WWBR 3. Development of criteria for reactor evaluation for use in the WWBR 4. Development of an integrated model to interrogate bioproduction from wastewater and determine product yields associated with wastewater treatment 5. Creation of new knowledge through the interpretation of the model on different wastewater systems. The wastewater biorefinery is defined as a bioproduction system that integrates multiple unit operations to deliver compliant water as well as a bioproduct or bioproducts. It is approached through the concepts of industrial metabolism and the circular economy. Wastewater biorefineries are shown in this work to be a viable approach to improving resource efficiency while ensuring the better ecological functioning of humans within “greater than human” systems. The work places emphasis on the recovery of bioproducts that conserve molecular complexity but acknowledges that energy production for use on site and in the immediate surroundings is always an important factor in the WWBR. This thesis introduces the need to include a qualitative way to evaluate the complexity of wastewater, in addition to standard classification of volume and concentration of components. Complexity includes both composition of potentially problematic compounds and how unpredictably it changes over time. In this approach, it is preferable to generate three types of products: products of sufficient value to be economically viable; products of variable value with concomitant assimilation of major contaminants; and clean water as a product, typically through multiple unit operations, allowing multi-criteria optimisation. Through this approach, multiple criteria can be met. Function-based products specific to niche industries, particularly those which produced the wastewater of interest, are of substantive interest owing to their streamlined market uptake. This thesis explores the requirements of the products that can be produced from wastewater in a non-sterile context and suggests product groupings that meet these requirements. Products secreted into the bulk volume are difficult to recover, leading preference to biomass associated and intracellular products. The product needs to offer a selective advantage to the organisms producing it to facilitate enrichment through, ecological selection of the microbial consortium with simultaneous cell retention through reactor design and operation. Four groupings of unit operations were reviewed in detail and evaluated with regards to their suitability to the wastewater biorefinery, using a two-part set of evaluation criteria that was developed in this work, considering the reactor design, and its operation. The four unit operations each contribute a specific role to the functioning of the WWBR as a system. It is acknowledged that not all units are commercially important, and that the concept of diminishing returns should be kept in mind. The heterotrophic microbial bioreactor, of which the bacterial biocatalyst is used as a representative example, is helpful for removing a high proportion of the organic carbon. A wide range of commodity products with market potential is known to be produced through heterotrophic microbial systems. Existing heterotrophic microbial reactor systems like the aerobic granular sludge system (AGS) exist that suit the wastewater biorefinery approach particularly well, while activated sludge along with biological nutrient removal (BNR), the most commonly used reactor system in South Africa, is the least suitable to the WWBR. The photo-mixotrophic reactor represented by the algal bioreactor is helpful to scavenge high proportions of nutrients, particularly nitrogen and phosphorus. The algal bioreactor is also known to produce commodity products. Photo-mixotrophic bioreactor systems complement the heterotrophic systems but are unlikely to be the dominant reactor due to land and energy requirements. The macrophytic bioreactor is targeted for polishing the exiting stream in terms of nitrogen, phosphorus and particulates to ensure compliant, fit for purpose water as a product, with a macrophyte-based byproduct. Macrophyte bioreactors, particularly floating wetlands, are promising tertiary systems that should be viewed in conjunction with water sensitive design principles to overcome potential land availability limitations. The solids bioreactor is an emerging beneficiation technology for biotransformation of bio-slurries and the solid phases recovered during WWBR operation to generate products of value, including biosolids. Solids bioreactors have great potential but require more investigation, with key challenges being mass transfer and separation technologies. Operating waste treatment facilities as net income-producing bioprocesses require a mindset change about investment, risk and associated returns. WWBRs require higher capital investment due to the additional process units and downstream processing required and have higher operating costs due to the greater control required during the process and greater number of operators with advanced skillsets. An identification of the relevant product range and comparison between conventional processing routes and those possible from the wastewater is required on a case by case basis, and an overview is given in this thesis. Waste may need to be re-classified to be used as an intermediate by-product or raw material, requiring legal considerations in terms of both the solid waste as per the National Environmental Management Act (NEMA) and liquid waste as per the National Water Act (NWA). The added complexity of reclassifying waste as raw material needs an acknowledgement of institutional challenges such as speaking across department silo’s. In this thesis, a model of these integrated unit operations was developed to generate material inventories across the system. This can be used to evaluate possible scenarios in an integrated context using a generic flowsheet as well as mass balances generated through the model. Three case studies were examined: municipal, abattoir and pulp and paper wastewater. Municipal wastewater was chosenas it represents a complex, dilute, 'suboptimal’ wastewater stream. Abattoir wastewater was chosen as an example of a complex, nutrient-concentrated stream that may be well suited to biological transformation. Pulp and paper wastewater was chosen as an example where the biorefinery concept is already well established, and is a low complexity, low nutrient, high carbon content stream. In considering the above case studies, a number of key learnings resulted. The impact of solids removal was clear and in keeping with existing bioprocessing and wastewater treatment principles of decoupling the hydraulic and solids residence times. Low nitrogen and phosphorus content in the pulp and paper wastewater as compared to the other two case studies indicated the need to conduct integrative studies of the unit operations to determine the most appropriate unit operations across the system. The effect of improving the product conversion yields and product recovery yields were examined, and a surprising result is the amount of nutrients that remain in compliant effluent, due to the large volumes of liquid involved. This leads to the conclusion that while the WWBR is a valuable way to address resource recovery, separation at source and internal process efficiencies are critical to improve overall resource efficiency and environmental protection. With regards to municipal wastewater, which contributes by far the most in terms of volume and nutrients of wastewaters in South Africa from the perspective of reactor design for waste(water) beneficiation, considering the cleaner production principle of separation at source, along with the need to decouple the solid and hydraulic residence times, dry sanitation presents a clear argument for the best WWBR approach. This approach must acknowledge that the transport of the sanitation raw materials is more difficult if hydro-transportation is not available, and needs to ensure operator equity, health and safety, particularly in the handling of the sanitation raw materials. This thesis was developed in conjunction with the Water Research Commission (WRC) project “Introducing the wastewater biorefinery concept: A scoping study of polyglutamic acid production from a Bacillus-rich mixed culture using municipal waste water” (Verster, et al., 2014) and Water Research Commission (WRC) K5/2380 project titled “Towards Wastewater Biorefineries: integrated bioreactor and process design for combined water treatment and resource productivity” (Harrison, et al., 2017). While the project focused on a global and national review on research on wastewater biorefineries and wastewater as a resource, this thesis explores in greater depth the requirements of each of the reactor units and their integration.